Adaptation of community-based distribution of family planning services to context-specific social networks: a case of marriage counsellors in Lusaka district, Zambia - Lucy Nyundo; Maxine Whittaker; Lynne Eagle; David R. Low (BMC, 2021)
Abstract Background The significant contribution of community-based distribution (CBD) of family planning services and contraceptives to the uptake of contraceptives in hard-to-reach communities has resulted in the scaling-up of this approach in many Sub-Saharan countries. However, contextual factors need to be taken into consideration. For example, social network influence (e.g. spouse/partner, in-laws, and parents) on fertility decisions in many African and Asian societies is inevitable because of the social organisational structures. Hence the need to adapt CBD strategies to the social network context of a given society. Methods Data collection involved structured interviews from August 2018 to March 2019. Randomly selected respondents (n = 149) were recruited from four purposively selected health facilities in Lusaka district, Zambia. Respondents were screened for age (> 15 yrs.) and marital status. A mix of categorical and qualitative data was generated. The Statistical Package for Social Sciences (SPSS®24) was used to carry out descriptive analysis and tests of association (Fisher's exact) while Nvivo®12 was used to analyse the qualitative data using a deductive thematic approach. Results The results indicate that pre-marriage counselling (pre-MC) influences key elements of the husband-wife relationship (p > 0.005), namely; sexual relationship, inter-personal communication, assignation of roles and responsibilities, leadership and authority. These elements of the husband-wife relationship also affect how spouses/partners interact when making fertility decisions. More importantly, the majority (86%) of the respondents indicated having a continuing relationship with their marriage counsellors because of the need to consult them on marital issues. Conclusion Marriage counsellors, though hardly reported in fertility studies, are important 'constituents' of the social network in the Zambian society. This is because marriage counsellors are trusted sources of information about marital issues and often consulted about family planning but perceived not to have the correct information about modern contraceptives. In this context, pre-MC offers a readily available, sustainable and culturally appropriate platform for disseminating accurate information about modern contraceptives provided in a private and personal manner. Therefore, the CBD strategy in Zambia can harness marriage counsellors by recruiting and training them as community agents.